2018
DOI: 10.3390/nu10111763
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Meal Timing on Postprandial Glucose Metabolism and Blood Metabolites in Healthy Adults

Abstract: We examined the effects of meal timing on postprandial glucose metabolism, including the incretin response and metabolites in healthy adults. Nineteen healthy young men completed two trials involving blood collection in a fasting state and at 30, 60 and 120 min after meal provision in a random order: (1) morning (~0900 h) and (2) evening (~1700 h). The blood metabolome of eight participants was analyzed using capillary electrophoresis-mass spectrometry. Postprandial glucose concentrations at 120 min (p = 0.030… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 48 publications
(88 reference statements)
2
42
0
Order By: Relevance
“…It is known that the metabolic dynamics are different in the morning and the evening, and morning metabolic dynamics are more active than evening metabolic dynamics [51]. Fish oil intake in the morning decreases serum and liver total cholesterol values compared to taking fish oil in the evening in HFD and high-fructose feeding model mice [23].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the metabolic dynamics are different in the morning and the evening, and morning metabolic dynamics are more active than evening metabolic dynamics [51]. Fish oil intake in the morning decreases serum and liver total cholesterol values compared to taking fish oil in the evening in HFD and high-fructose feeding model mice [23].…”
Section: Discussionmentioning
confidence: 99%
“…LAT4 shows high activity under dephosphorylated condition, suggesting that post-translational modulation such as phosphorylation could be involved in the time-dependent amino acid absorption. In studies involving human subjects, comparing the postprandial response between morning and evening using metabolomics, revealed that 16 amino acids such as arginine and leucine were detected at higher levels in blood in the morning than in the evening (59). These data suggest that the postprandial amino acids response in humans depends on the feeding time.…”
Section: Amino Acid Metabolismmentioning
confidence: 97%
“…The energy of the test meal was distributed as follows: 15% from fat, 70% from carbohydrates, and 15% from protein. This percentage of carbohydrate loading could potentially increase postprandial glucose in healthy adults [26,27]. All participants were asked to consume the test meal within 20 min.…”
Section: Test Mealsmentioning
confidence: 99%